The impact of government environmental attention on public health: Implications for corporate sustainable development - Tian, Jinfang; Zhang, Shu; Wei, Xudong; Zhuang, Shan; Zhang, Mingxuan (Frontiers in Environmental Science, 2022)
As major contributors to air pollution, enterprises have a growing impact on the environment, which puts public health at risk and necessitates urgent government intervention. This study constructs a government environmental attention variable through employing the textual analysis of Chinese government work reports from 2004 to 2017 to examine the impact of government environmental attention on public health. We find that local government environmental attention has a significant and positive impact on public health. Our mechanism analysis indicates that government environmental governance investment acts as an important mediating channel in the relationship between government environmental attention and public health. Moreover, we find that the impact of government environmental attention on public health is more pronounced in Central and Western China, in low-openness regions, and after the incorporation of environmental performance in the cadre evaluation system in 2006. Our study links micro-level environmental issues with macro-level governmental behaviors, which offers a new perspective for future research on the influencing factors of public health and has practical implications for corporate sustainable development.